Effect of Fresh Vinasse Application on Soil Chemical Characteristics - Simping Yuliatun; Firmansyah Bagus Ilham Akbar (Pusat Penelitian Perkebunan Gula Indonesia, 2022)
The application of fresh vinasse waste is still controvertion. The objective of this research was to determine the effect of the doses of vinasse given on land on chemical characteristics for soil quality. It was conducted in a randomized block design with 4 doses of vinasse in 3 replications. There were 4 kinds of vinasse doses, namely 75,000, 150,000, 225,000 and 300,000 litres/ha. The control was the administration of 0 litre of vinasse, in which sampling was carried out at the beginning before the land was sprayed vinasse. Statistical design for analysis of chemical data including the element of phosphorous, potassium, nitrogen, C/N ratio, humic substances, pH, organic matter, and cation exchange capacity (CEC) were analyzed by One-way ANOVA. The average value of the treatment was tested with a least significant difference test (LSD) with a control comparison. The results showed that the dose of vinasse sprayed to land between 75,000 to 300,000 liters/ha had a significant effect on the increasing in nitrogen content, C/N ratio, phosphorus, potassium, cation exchange capacity and humic substances when compared to the control. Meanwhile, the soil pH conditions between control and treatments with vinasse dose were not significantly different. Sprayed of vinasse to the land up to a dose of 300,000 litres/ha showed a positive effect on soil quality and soil fertility.